2016
DOI: 10.1111/hsc.12380
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the health needs of older people with intellectual disabilities: exploring the experiences of residential social care staff

Abstract: Older people with intellectual disabilities often experience high levels of health needs and multiple morbidities but they may be supported by residential care staff with little or no previous experience of identifying and meeting health needs. Little is known regarding how they undertake this health-related role and this exploratory study seeks to address this gap. A purposive sample of 14 managers of supported living accommodation in Wales were interviewed in 2014 to determine their experiences of supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…One study used semistructured interviews with managers of supported living accommodation to explore how residential social care staff support older people with ID to meet their health needs. 43 This study found that residential social care staff often felt that their role in recognising, monitoring and meeting clients' health needs was not always understood by health professionals and that this had an impact on their ability to meet these needs.…”
Section: Carer Knowledge/skillsmentioning
confidence: 85%
See 3 more Smart Citations
“…One study used semistructured interviews with managers of supported living accommodation to explore how residential social care staff support older people with ID to meet their health needs. 43 This study found that residential social care staff often felt that their role in recognising, monitoring and meeting clients' health needs was not always understood by health professionals and that this had an impact on their ability to meet these needs.…”
Section: Carer Knowledge/skillsmentioning
confidence: 85%
“…Fourteen studies reported in 16 publications, published from 2003 to 2017, were included in this group (Table 12). Of these, three dealt with general practice, 44,45,48 three dealt with a range of primary care services, 36,37,49 three dealt with carers working at residential or supported living homes [33][34][35]43 and two dealt with formal and informal carers of people with ID in residential or family homes. 38,39 The other three studies dealt with audiology services, 42 cervical and cancer screening 40 and sexual health.…”
Section: Identifying Needmentioning
confidence: 99%
See 2 more Smart Citations
“…The time and continuity of the relationship between the person with an ID and staff as well as knowledge support from colleagues and managers were considered as important prerequisites for the detection of possible signs of dementia and the adaptation of the caring process in the interviews. Northway [ 27 ] argues that staff who are close to the person with ID have a unique knowledge of changes in health conditions and, therefore, points to the importance of respecting the knowledge that staff have access to. Llewellyn [ 28 ] indicates that the unique knowledge of staff represents a crucial prerequisite for starting a care process designed to discover dementia and adapt support based on changing needs.…”
Section: Discussionmentioning
confidence: 99%